Rheumatoid Arthritis and Autoimmune Hemolytic Anemia as First Manifestation of Rhupus - Alejandra Espinosa-Orantes; Martha Adriana Hernandez-Vera; Jose Daniel Juarez-Villa; Gutiérrez-Espinoza Anahí Guadalupe; Guillermo Flores (Case Reports in Rheumatology)
“Rhupus” syndrome is a rare condition that describes the coexistence of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), which prevalence among patients with SLE varies from 0.01% to 9.7%. There are few reported cases of the association between autoimmune hemolytic anemia and rheumatoid arthritis with systemic lupus erythematosus (rhupus). We report a rare case of rhupus in a 29-year-old woman, associated with autoimmune hemolytic anemia.